2005
DOI: 10.1007/s10327-005-0196-1
|View full text |Cite
|
Sign up to set email alerts
|

Possible roles and functions of LPL1 gene encoding lysophospholipase during early infection by Magnaporthe grisea

Abstract: The rice blast fungus Magnaporthe grisea differentiates appressoria, which are required to attack its rice plant host. Clone A26, tentatively named LPL1, was previously found to be homologous to the known lysophospholipase genes from our subtractive cDNA library. The LPL1 protein had a consensus motif (GxSxG) and a catalytic triad (S, D, H) of esterases in the deduced amino acid sequence, and the protein expressed in Escherichia coli had lysophospholipase activity. To clarify the functions and possible roles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In addition to our study, there is one report of a cellular phenotype associated with an APT1/LysoPLA1 mutation. Gene replacement of the Magnaporthe grisea LPL1 gene caused defects in apressoria formation and penetration into leaf cells (Kanamori et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our study, there is one report of a cellular phenotype associated with an APT1/LysoPLA1 mutation. Gene replacement of the Magnaporthe grisea LPL1 gene caused defects in apressoria formation and penetration into leaf cells (Kanamori et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The biological and cytological properties of fungi change from the mycelial base to the top, 12,13) and different genes are expressed in the germ tube than in the vegetatively growing mycelium, 14,15) therefore, these differences can affect the activity of mepanipyrim. However, our results suggested that the differences in mepanipyrim activities on germ tubes and mycelia correlate with the age of the culture.…”
Section: Discussionmentioning
confidence: 99%
“…Next, this gene expression was analyzed in more detail, and genes upregulated in appressorium-forming conditions compared with vegetatively growing mycelia were isolated as candidate genes related to appressorium formation. To elucidate the function of the isolated genes, we generated null mutants of each gene and characterized their phenotypes (Kamakura et al 2002;Saitoh et al 2003;Kanamori et al 2005). In addition, to enhance the analysis of the genes, we developed a GFP-tagging gene knockout (GGKO) method that enables expression and functional analysis of a gene simultaneously (Saitoh et al 2008) and devised a simple method to obtain fungal DNA for molecular biological analyses (Saitoh et al 2006).…”
Section: Exploration Of the Genes Related To Appressorium Formationmentioning
confidence: 99%